Strategi Guru dalam Mengembangkanv Pembelajaran Kreatid dan Inovatif Pada Pembelajaran Pendidikan Agama Islam - Ilham, Ilham; Nasaruddin, Nasaruddin; Ruslan, Ruslan (Peneliti.net, 2025)
To help develop students' potential and creativity in many ways, teachers must be able to teach in a planned, creative, interactive, and innovative way. They must also be able to overcome student frustration, share time and experience with students, and build positive relationships with students. The purpose of this study is to find out and understand how teachers can use innovative and creative approaches in Islamic Religious Education learning so that Islamic Religious Education learning can achieve optimal results. This study uses a qualitative approach to describe and explain how teachers contribute to the development of innovative and creative learning in Islamic Religious Education. To obtain this data, expert opinions are used. According to this study, teachers must be creative and innovative in managing the learning process. Creative learning here can be interpreted as learning that creates a new model or approach or modifies existing teaching methods. While innovative learning is learning that is fun, interesting, and functionally facilitates the development of children's growth and development. Innovative is renewal, unique, and modern.